Conflictos geopolíticos por el agua en las cuencas mineras del Departamento de Oruro, Bolivia - Víctor Hugo Perales Miranda (VertigO, 2010)
In this paper, it is analyzed geopolitical water conflicts between involved actors in mining pollution of sub basins of Poopó Lake in Oruro, in the southwestern zone of Bolivia. For that purpose, it is described social and hydrological aspects, moreover, interaction between actors from an analysis of the social building of territory.